Implementación de un sistema de gestión documental para el archivo inactivo de la universidad Antonio Nariño sede Villavicencio (2020)
The implementation of a document management system (SGD) for the inactive archive of the Antonio Nariño University (UAN), Villavicencio headquarters, was proposed because the inactive archive of the UAN has made the processes of how academic documents are managed difficult. , so they are unaware of archival techniques; From this arises the need to carry out a good management of the documents that are kept in the documentary heritage at the Villavicencio headquarters. In this research project a descriptive methodology was used, in which a diagnosis was carried out on the current state of the inactive file area of the UAN, Villavicencio headquarters, it was observed that the documents are not being managed correctly ; This information was recorded in a field diary as a technical tool for data collection, with the information collected, the elaboration of the classification tables (CCD), valuation (TVD), retention (TRD) and documentary inventory was continued for keep control of the academic documents that are stored in the inactive archive, guaranteeing their correct conservation; This allows the University to improve the management of information on the handling that must be given to documents under archiving regulations